A Partial Credit Guarantee : Enhancing Access to Credit Markets during Constrained Times - Zaman Khan, Isfandyar (International Finance Corporation, Washington, DC, 2015)
To Croatia, the ripples of the European financial crisis felt more like large waves! The challenging market conditions limited the ability of the Croatian Bank for Reconstruction and Development (HBOR) to raise funds efficiently without credit enhancement. This in turn impeded a steady flow of credit to the private sector, which was necessary to enhance competitiveness ahead of Croatia s entry to the European Union in July 2013. In response to a request from the Croatian government, the World Bank decided that a Partial Credit Guarantee (PCG) would be the ideal instrument to assist HBOR.